Evaluasi Program Pembelajaran Ilmu Pengetahuan Sosial di SMP Negeri Kota Ambon - Gesia Mira Urlialy; Kurniawati Kurniawati; Nurzengky Ibrahim (Jurnal Pendidikan Sejarah, 2018)
This study aims to evaluate historical learning programs that are integrated in social science to provide information on the extent of achievement of historical material integrated in social studies using the evaluative approach of the CIPP model (Context, Input, Process, and Product). This research was conducted at Ambon City Junior High School VII grade. The findings in this study on the context component indicate that the level of actualization in four aspects is moderate; in the input component the actualization level in three low aspects and two aspects shows the level of moderate actualization. In the input component the level of actualization in supporting the implementation of social studies learning in two low aspects and three moderate asepek. In the process component, the level of actualization in the implementation of social studies, especially historical material; and on the product component the actualization level of student learning outcomes is very high. Based on this research, it can be concluded that history learning integrated in social studies at Ambon City Junior High School in class VII is not optimal. Improvements need to be made - reforms by the principal, teachers and the government to support historical learning programs integrated in social studies. Keywords: Learning Social Sciences, History, CIPP Model, Program Evaluation. Abstrak: Penelitian ini bertujuan untuk mengevaluasi program pembelajaran sejarah yang terintegrasi dalam ilmu pengetahuan sosial untuk memberikan informasi sejauh mana ketercapaian dari materi sejarah yang terintegrasi dalam IPS dengan menggunakan pendekatan evaluatif model CIPP (Context, Input, Process, and Product). Penelitian ini dilakukan di Sekolah Menengah Pertama Kota Ambon kelas VII. Temuan dalam penelitian ini pada komponen konteks menunjukkan bahwa tingkat aktualisasi pada empat aspek sedang; pada komponen input tingkat aktualisasi pada tiga aspek rendah dan dua aspek menunjukkan tingkat aktualisasi sedang. Pada komponen input tingkat aktualisasi dalam menunjang pelaksanaan pembelajaran IPS sejarah pada dua aspek rendah dan tiga asepek sedang. Pada komponen proses tingkat aktualisasi dalam pelaksanaan pembelajaran IPS khusunya materi sejarah sedang; dan pada komponen produk tingkat aktualisasi terhadap hasil belajar siswa sangat tinggi. Berdasarkan penelitian ini dapat disimpulkan bahwa pembelajaran sejarah yang terintegrasi dalam IPS di Sekolah Menengah Pertama Kota Ambon kelas VII belum optimal. Perlu dilakukan pembenahan – pembenahan oleh pihak kepala sekolah, guru dan pemerintah untuk mendukung program pembelajaran sejarah yang terintegrasi dalam IPS. Kata Kunci: Pembelajaran Ilmu Pengetahuan Sosial, Sejarah, Model CIPP, Evaluasi Program.